The role of the cardiomyocyte circadian clocks in ion channel regulation and cardiac electrophysiology. (7th April 2022) - Schroder, Elizabeth A.; Ono, Makoto; Johnson, Sidney R.; Rozmus, Ezekiel R.; Burgess, Don E.; Esser, Karyn A.; Delisle, Brian P.
Abstract: Daily variations in cardiac electrophysiology and the incidence for different types of arrhythmias reflect ≈24 h changes in the environment, behaviour and internal circadian rhythms. This article focuses on studies that use animal models to separate the impact that circadian rhythms, as well as changes in the environment and behaviour, have on 24 h rhythms in heart rate and ventricular repolarization. Circadian rhythms are initiated at the cellular level by circadian clocks, transcription–translation feedback loops that cycle with a periodicity of 24 h. Several studies now show that the circadian clock in cardiomyocytes regulates the expression of cardiac ion channels by multiple mechanisms; underlies time‐of‐day changes in sinoatrial node excitability/intrinsic heart rate; and limits the duration of the ventricular action potential waveform. However, the 24 h rhythms in heart rate and ventricular repolarization are primarily driven by autonomic signalling. A functional role for the cardiomyocyte circadian clock appears to buffer the heart against perturbations. For example, the cardiomyocyte circadian clock limits QT‐interval prolongation (especially at slower heart rates), and it may facilitate the realignment of the 24 h rhythm in heart rate to abrupt changes in the light cycle. Additional studies show that modifying rhythmic behaviours (including feeding behaviour) can dramatically impact the 24 h rhythms in heart rate and ventricular repolarization. If these mechanisms are conserved, these studies suggest that targeting endogenous circadian mechanisms in the heart, as well as modifying the timing of certain rhythmic behaviours, could emerge as therapeutic strategies to support heart function against perturbations and regulate 24 h rhythms in cardiac electrophysiology. Abstract : Abstract figure legend Time‐of‐day variations in cardiac electrophysiology and the incidence of arrhythmogenic events are generated by endogenous circadian rhythms, 24 h rhythms in the environment and 24 h rhythms in behaviour. This article focuses on studies that use animal models to separate the impact that circadian clocks (ubiquitously expressed transcription–translation feedback loops that initiate circadian rhythms), daily changes in the light cycle and daily changes in the timing of feeding have on 24 h rhythms in cardiac electrophysiology. Studies now show that the circadian clock mechanism in the heart regulates the expression of cardiac ion channels; underlies time‐of‐day changes in intrinsic sinoatrial node excitability; and shapes the ventricular action potential waveform. Additional studies show that modifying the light cycle and rhythmic feeding behaviour can dramatically impact the 24 h rhythms in cardiac electrophysiology. If conserved, these studies suggest that targeting endogenous circadian clock mechanisms in the heart, as well as modifying 24 h rhythms in the environment and behaviour, could emerge as therapeutic strategies to support normal cardiac electrophysiology and mitigate the risk of arrhythmogenic events.